Drivers and effects of fish-for-sex related single parenthood in a fishing coastal community in Ghana - Sylvester Kyei-Gyamfi; Frank Kyei-Arthur (PLoS ONE, 2025)
The migration of fishers from one community to another is often associated with fish-for-sex (FFS) exchanges. FFS can lead to social issues such as absentee parenting and the generational cycle of FFS relationships. This study examined the perception of the frequency of FFS-related female single parenthood and the drivers and effects of single parenthood arising from FFS relationships in Elmina, Ghana. This study used a convergent parallel mixed-methods design to examine the views of 385 fishers, 30 key informants, and 20 focus group participants on FFS-related single parenthood. Descriptive statistics was used to analyze the quantitative data, while the transcript of participants were analyzed thematically. The findings show that most fishers (63.1%) indicated the occurrence of FFS female single parenthood in Elmina. The driver of FFS female single parenthood included uncertain paternity resulting from multiple sexual partners and male partners denial of paternity due to suspicions of promiscuity. Also, the adverse effects of FFS female single parenthood included paternal absence, child developmental challenges, maternal burden, and the intergenerational cycle of FFS relationships. This study demonstrated that FFS female single parenthood is a common phenomenon in Elmina. There is an urgent need for policymakers to design interventions to address the phenomenon of FFS female single parenthood to enhance the well-being of children and mothers with children from FFS relationships.